PERAN MUSIK ORGAN DALAM MUSIK LITURGI - Perseveranda Putra Korsini; Petrus Klaver Pena (STKIP Citra Bakti, 2026)
Histori artikel This study aims to examine students'perceptions of modern classical music within social, cultural, cognitive, and aesthetic contexts. The development of digital technology has expanded students' access to various music genres, including modern classical music; however, this increased access is not always accompanied by an increase in appreciation. Students' perceptions of modern classical music are still influenced by cultural stereotypes, educational backgrounds, listening experiences, as well as the social meaning of classical music as part of elite culture. This research employs a descriptive qualitative approach, involving students from diverse educational backgrounds as subjects. Data were collected through in-depth interviews, open-ended questionnaires, and documentation studies, and were then analyzed thematically. The results indicate that students' perceptions of modern classical music are diverse, ranging from interest and positive appreciation to unfamiliarity and a psychological distance from the genre. Targeted exposure, music education, and an understanding of aesthetic and historical contexts were proven to play an important role in shaping positive student attitudes. This study concludes that students' perceptions of modern classical music are not solely determined by media access but are also shaped by social constructions and their musical experiences. These findings are expected to serve as a foundation for developing more inclusive and relevant music education strategies in the university environment. Abstract Penelitian ini bertujuan untuk mengkaji persepsi mahasiswa terhadap musik klasik modern dalam konteks sosial, kultural, kognitif, dan estetika. Perkembangan teknologi digital telah memperluas akses mahasiswa terhadap berbagai genre musik, termasuk musik klasik modern, namun peningkatan akses tersebut tidak selalu diikuti oleh peningkatan apresiasi. Persepsi mahasiswa terhadap musik klasik modern masih dipengaruhi oleh stereotip budaya, latar belakang pendidikan, pengalaman mendengar, serta pemaknaan sosial terhadap musik klasik sebagai bagian dari budaya elit. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan melibatkan mahasiswa dari berbagai latar belakang pendidikan sebagai subjek penelitian. Data dikumpulkan melalui wawancara mendalam, kuesioner terbuka, dan studi dokumentasi, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa persepsi mahasiswa terhadap musik klasik modern bersifat beragam, mulai dari ketertarikan dan apresiasi positif hingga sikap kurang familiar dan jarak psikologis terhadap genre tersebut. Paparan yang terarah, edukasi musik, serta pemahaman konteks estetika dan historis terbukti berperan penting dalam membentuk sikap positif mahasiswa. Penelitian ini menyimpulkan bahwa persepsi mahasiswa terhadap musik klasik modern tidak hanya ditentukan oleh akses media, tetapi juga oleh konstruksi sosial dan pengalaman bermusik yang dimiliki. Temuan ini diharapkan dapat menjadi dasar bagi pengembangan strategi pendidikan musik yang lebih inklusif dan relevan di lingkungan perguruan tinggi. .